2017
DOI: 10.1080/01576895.2017.1326828
|View full text |Cite
|
Sign up to set email alerts
|

Volunteers in Australian archives

Abstract: Why do volunteers choose to contribute thousands of unpaid hours per week to Australian archives? This paper presents the results of a nationwide web survey that provides insight into the demographics, motivations and experiences of volunteers in Australian archives. The findings provide a representative overview of formal volunteers in Australian archives, determining 'who' they are, the value of the contributions they provide and the level of training and support offered to them. This study is a continuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Across classification methods, the most frequently mentioned reasons for volunteering were (a) interest in the activities of the organisation (e.g., dressing up as a historical figure), (b) social interaction and family involvement, pro‐social motives (e.g., helping others), (c) self‐development (e.g., learning and career building), and (d) enjoyment and recreation. De Villiers, Laurent, and Stueven () found that volunteers at archival organisations across Australia were mainly motivated by the content of their work and subsequently by the social connections that they experienced through their volunteering. Phillips, Andrews, and Hickman () found that hospice volunteers in NSW mainly volunteered to make a difference, including believing in the values of the cause, and for personal development, such as personal growth and skills development.…”
Section: Becoming a Volunteermentioning
confidence: 99%
See 1 more Smart Citation
“…Across classification methods, the most frequently mentioned reasons for volunteering were (a) interest in the activities of the organisation (e.g., dressing up as a historical figure), (b) social interaction and family involvement, pro‐social motives (e.g., helping others), (c) self‐development (e.g., learning and career building), and (d) enjoyment and recreation. De Villiers, Laurent, and Stueven () found that volunteers at archival organisations across Australia were mainly motivated by the content of their work and subsequently by the social connections that they experienced through their volunteering. Phillips, Andrews, and Hickman () found that hospice volunteers in NSW mainly volunteered to make a difference, including believing in the values of the cause, and for personal development, such as personal growth and skills development.…”
Section: Becoming a Volunteermentioning
confidence: 99%
“…First, agreeableness is the tendency to be tolerant, good‐natured, and cooperative (Lee & Ashton, ), which is related to “giving back to the community,” the number one reason for volunteering identified in several studies (e.g., Dolnicar & Randle, ; Hyde & Knowles, ; Zappalà & Burrell, ). Second, extraversion is the tendency to be gregarious and seek out social situations (Lee & Ashton, ), which could very well be associated with another frequently reported reason to volunteer—“to connect with others” (e.g., Anderson & Shaw, ; De Villiers et al, ).…”
Section: Becoming a Volunteermentioning
confidence: 99%